Evaluation of the antioxidant activity of amarnathus spinosus Linn., by non enzymatic haemoglycosylation - B.S. Ashok Kumar; K. Lakshman; K.N. Jayaveera; Saleemulla Khan; B. Manoj; V.B. Narayan Swamy (Universiti Kebangsaan Malaysia, 2010)
Amaranthus spinosus Linn. complete plant material was extracted successively by petroleum ether, chloroform, methanol, and water. All the extracts were subjected to in vitro non-enzymatic haemo-glycosylation method, i.e. an oxidation reaction. The degree of haemoglycosylation in the presence of different extracts of Amaranthus spinosus were measured colorimetrically at 520 nm. The preventive effect of haemoglobin glycosylation at the two concentration; 0.5 and 1 mg/mL was estimated as follows: pet. ether; 13.1%, 16.4%, chloroform; 5.7%, 12%, methanol: 36.91%, 56.07% and aqueous: 22.2%, 31.01 %, respectively. The α-tocopheral (Vitamin E) was used as standard.